Total-Body Dynamic Imaging and Kinetic Modeling of [ 18 F]F-AraG in Healthy Individuals and a Non–Small Cell Lung Cancer Patient Undergoing Anti–PD-1 Immunotherapy - Omidvari, Negar; Levi, Jelena; Abdelhafez, Yasser G.; Wang, Yiran; Nardo, Lorenzo; Daly, Megan E.; Wang, Guobao; Cherry, Simon R. (Journal of Nuclear Medicine, 2024)
Immunotherapies, especially checkpoint inhibitors such as anti-programmed cell death protein 1 (anti-PD-1) antibodies, have transformed cancer treatment by enhancing the immune system's capability to target and kill cancer cells. However, predicting immunotherapy response remains challenging. F-arabinosyl guanine ([ F]F-AraG) is a molecular imaging tracer targeting activated T cells, which may facilitate therapy response assessment by noninvasive quantification of immune cell activity within the tumor microenvironment and elsewhere in the body. The aim of this study was to obtain preliminary data on total-body pharmacokinetics of [ F]F-AraG as a potential quantitative biomarker for immune response evaluation. The study consisted of 90-min total-body dynamic scans of 4 healthy subjects and 1 non-small cell lung cancer patient who was scanned before and after anti-PD-1 immunotherapy. Compartmental modeling with Akaike information criterion model selection was used to analyze tracer kinetics in various organs. Additionally, 7 subregions of the primary lung tumor and 4 mediastinal lymph nodes were analyzed. Practical identifiability analysis was performed to assess the reliability of kinetic parameter estimation. Correlations of the SUV , the tissue-to-blood SUV ratio (SUVR), and the Logan plot slope ( ) with the total volume of distribution ( ) were calculated to identify potential surrogates for kinetic modeling. Strong correlations were observed between and SUVR with , suggesting that they can be used as promising surrogates for , especially in organs with a low blood-volume fraction. Moreover, practical identifiability analysis suggested that dynamic [ F]F-AraG PET scans could potentially be shortened to 60 min, while maintaining quantification accuracy for all organs of interest. The study suggests that although [ F]F-AraG SUV images can provide insights on immune cell distribution, kinetic modeling or graphical analysis methods may be required for accurate quantification of immune response after therapy. Although SUV showed variable changes in different subregions of the tumor after therapy, the SUVR, , and showed consistent increasing trends in all analyzed subregions of the tumor with high practical identifiability. Our findings highlight the promise of [ F]F-AraG dynamic imaging as a noninvasive biomarker for quantifying the immune response to immunotherapy in cancer patients. Promising total-body kinetic modeling results also suggest potentially wider applications of the tracer in investigating the role of T cells in the immunopathogenesis of diseases.